2017
DOI: 10.1017/s0022149x17000049
|View full text |Cite
|
Sign up to set email alerts
|

Intraguild interactions between five congeneric species ofThaparocleidus(Monogenoidea) from the freshwater sharkWallago attu, Lucknow, India

Abstract: The fish host (Wallago attu) and monogenoid parasite (Thaparocleidus sp.) have been recorded during 2 years (2011 and 2012) to investigate intra/interspecific interactions among query species (T. sudhakari (Gusev, 1976) Lim, 1996; T. indicus (Kulkarni, 1969) Lim, 1996; T. gomtius (Jain, 1952) Lim, 1996; T. yogendraii Agrawal, 1981 and T. wallagonius Jain, 1952) in the light of parasitic worm burden, morphological and molecular data. Each species is highly host specific (oioxenous), with a specialized functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 46 publications
(57 reference statements)
1
6
0
Order By: Relevance
“…We found that monogeneans aggregate both at the population level and between species. These patterns have been previously described in ectoparasite communities of fish (Rohde et al, 1995; Morand et al, 1999; Simková et al, 2000, 2001; Agrawal et al, 2017). We observed that intraspecific aggregation (J) of the most abundant species increase with the intensity of the infection.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…We found that monogeneans aggregate both at the population level and between species. These patterns have been previously described in ectoparasite communities of fish (Rohde et al, 1995; Morand et al, 1999; Simková et al, 2000, 2001; Agrawal et al, 2017). We observed that intraspecific aggregation (J) of the most abundant species increase with the intensity of the infection.…”
Section: Discussionsupporting
confidence: 76%
“…Simková et al (2000) did not find negative interactions, and based on the absence of negative correlations between the abundances among species pairs, argued that only when high population densities were achieved could competition play an important role. Agrawal et al (2017) evaluated 10 combinations of five species of congeneric monogeneans in 72 Wallago attu freshwater sharks in India, from which 10,920 monogeneans were recovered at an average of 151 individuals per fish examined. Populations of Thaparocleidus were aggregated (J > 0); they found that J positively correlated with the intensity of the infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In species-rich parasitic communities that have high abundances, such as bird communities, both interspecific and intraspecific interactions among parasites are important forces that structure the community (e.g., Bush & Holmes, 1986;Stock & Holmes, 1988). In some fishes, mostly elasmobranchs, rich helminth communities have been described and interactions between species have been documented (e.g., Agrawal, Rajvanshi, & Asthana, 2017;Randhawa, 2012).…”
Section: Introductionmentioning
confidence: 99%